Answer:
The "x² + bx + c = 0" ; is treated as:
"x² + (-b)x + (-c) = 0 " ;
or, put simply:
___________________________________
" x² − bx − c = 0 ;
in which: b = - (insert number);
and "c" = - (insert number);
___________________________________
Then, the expression on the "left-hand side" of the equation is "factored"; and set equal to "0" .
___________________________________
Note of interest: This is done even if "factoring" cannot be done; and/or if one wishes to proceed using the "quadratic equation formula" to solve for "x".
___________________________________
Hope this helps!